The Influence Of Work Motivation, Organizational Climate, Intellectual Intelligence And Emotional Intelligence On The Work Achievement Of Teacher At Dismp Negeri 5 Muara Enim - Aisyah Aisyah; Sulbahri Madjir; Darmin Darmin (Penerbit Jurnal Indonesia, 2023)
This study aims to influence work motivation, organizational climate, intellectual intelligence, emotional intelligence on teacher achievement at SMP Negeri 5 Muara Enim. The type of research used in this research is quantitative research. The data in this study used primary data using research data collection techniques and questionnaires. The research used a survey method, the research respondents were some 35 teachers. Questionnaire instruments regarding work performance as related variables, division of tasks, coaching, work skills and organizational commitment as independent variables and analysis tools using multiple regression. From the results of the study it was found that the influence of work motivation, organizational climate, intellectual intelligence, emotional intelligence partially has a significant influence on work performance. Coaching partially has a significant effect on work performance. Organizational climate partially has a significant influence on achievement. Intellectual intelligence commitment, emotional intelligence partially and correlation have a significant effect on teacher achievement at SMP Negeri 5 Muara Enim